UPAYA PAKSA BADAN (LIJFSDWANG) TERHADAP DEBITOR YANG TIDAK KOOPERATIF - Yolanda, Nina (Solusi, 2018)
Objective: To analyze and describe the forced effort of the body (lijfsdwang) against uncooperative debtors. Research method: research using normative juridical method. The results of the study: Requested the supervisory judge to issue a summons with the objective of presenting the debtor's bankruptcy debtor to the meeting or creditors meeting, delivering a warning letter instructing the debtor to comply with specific actions in bankruptcy, asking the supervisory judge to use the instruments available in Article 84 of the Law, ie to hold the debitor hostage. The weakness of bankruptcy law enforcement is due to: the lack of goodwill of the court (Commercial Court) to carry out the body's forced efforts only for trivial reasons; the reason for the forced implementation of the body in the UUK is easily avoided by uncooperative uncooperative debtors, whereas the reason for the institution's implementation of agency force is to impose coercion on debtors who are able to pay but do not pay their debts to creditors, so they do not hang around and hide even the master property that has been declared bankrupt.Ketentuan this naughty debtor shelter from the threat of force body. The debtor can easily meet both criteria in the provisions of this UUK. Therefore, the authors suggest that a revision of the provision of force in this UUK